Upper Gastrointestinal Abnormalities in Esophagogastroduodenoscopy Examination: Descriptive Study in PSUPAU Endoscopic Unit - Julwan Pribadi; Sedijono Sedijono; Suryantini Suryantini; Marcellus Simadibrata; Ari Fahrial Syam; Murdani Abdullah; Achmad Fauzi; Dadang Makmun; Chudahman Manan; Daldiyono Daldiyono; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2008)
Background: The Endoscopy Unit of Indonesian Air Force Central Hospital Dr. Esnawan Antariksa, Jakarta, Indonesia, has just been established in late 2004 and it is still in developing process. This study was aim to depict the profile of patients who underwent esophagogastroduodenoscopy procedure in the unit. Method: This study was a retrospective study that analyzed data in endoscopic registry of patients who underwent esophagogastroduodenoscopy (EGD) examination from September 2004 to December 2007. Result: Total of 108 patients underwent EGD examination, comprised of 66 (61%) males and 42 (39%) females, with average age of 45.4 years old (range 16-77 years old). The most frequent indication for EGD was dyspepsia 63%, followed by hematemesis-melena 26% and dysphagia 5.5%. Among patients with dyspepsia, EGD revealed organic abnormalities in 71% patients, with descriptions of erosive gastritis 35%, gastritis 18%, bile reflux 7%, esophagitis 5% and gastric ulcer 3%. Among patients with hematemesis-melena, EGD revealed abnormalities, which were described as erosive gastritis 48%, esophageal varices bleeding 22%, gastric ulcer 18%, caustic injury 4%, and esophagitis 4%. Conclusions: EGD is an important procedure to ascertain the occurence of organic abnormalities in patient with gastrointestinal symptoms and signs e.g. dyspepsia and gastrointestinal bleeding. More than half of patients with dyspepsia showed organic abnormalities. Among patients with hematemesis-melena, erosive gastritis is more common than variceal bleeding. Keywords: esophagogastroduodenoscopy, dyspepsia, upper gastrointestinal bleeding, hematemesis melena